How to prove:

$$ \sum_{n=0}^{\infty}\left[\,\sum_{k=1}^{a}\frac{1}{a\,n+k}-\sum_{k=1}^{b}\frac{1}{b\,n+k}\,\right]=\log\left(\frac{a}{b}\right)\qquad\colon\,a\,,b\in\mathbb{N}^{+}\tag{1}$$

Obviously, we cannot split the sum: $$ \left(\sum_{n=0}^{\infty}\,\sum_{k=1}^{a}\frac{1}{a\,n+k}\right)-\left(\sum_{n=0}^{\infty}\,\sum_{k=1}^{b}\frac{1}{b\,n+k}\right) = \left(\sum_{n=1}^{\infty}\frac1n\right)-\left(\sum_{n=1}^{\infty}\frac1n\right)=\infty-\infty $$ Any ideas? Thanks in advance.


For starters, let us give an integral representation to the general term of the outer sum:

$$ \sum_{k=1}^{a}\frac{1}{an+k}-\sum_{k=1}^{b}\frac{1}{bn+k} = \int_{0}^{1}\left(x^{an}\sum_{k=1}^{a}x^{k-1}-x^{bn}\sum_{k=1}^{b}x^{k-1}\right)\,dx \tag{1}$$ turning the whole sum into: $$ \lim_{N\to +\infty}\sum_{n= 0}^{N}\int_{0}^{1}\left[\left(x^{an}-x^{bn}\right)-\left(x^{a(n+1)}-x^{b(n+1)}\right)\right]\,\frac{dx}{1-x} \tag{2}$$ If now we exploit $$ \int_{0}^{1}\frac{x^A-x^B}{1-x}\,dx = H_B-H_A \tag{3}$$ the whole sum turns into $$ \lim_{N\to +\infty} \left(H_{aN}-H_{bN}\right) = \log\frac{a}{b} \tag{4}$$ due to $H_n=\log(n)+\gamma+O\left(\frac{1}{n}\right).$

It is interesting to point out that we are not allowed to exchange $\sum_{n\geq 0}$ and $\int_{0}^{1}$ in $(2)$, since the hypothesis of the dominated convergence theorem are not met.

  • $\begingroup$ I was just typing the same approach (+1). $\endgroup$ – Zaid Alyafeai Feb 28 '17 at 22:36
  • 2
    $\begingroup$ You don't have to get an integral out to do this: you can see just by writing out the sums carefully that the partial sum is $H_{aN}-H_{bN}$. $\endgroup$ – Chappers Feb 28 '17 at 22:40
  • 2
    $\begingroup$ Your answering speed is away beyond expectations (^_^)! Thanks Jack. (+1) $\endgroup$ – Hazem Orabi Feb 28 '17 at 22:43

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.